Environmental Sustainability Practices in Supply Chains and Manufacturing Firms’ Performance: Evidence from Tanzania Breweries Limited - Mwansasu, Elinala Lutufyo; Mwagike, Leonada Raphael (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose- This study investigates the influence of environmental sustainability practices in supply chains on the performance of manufacturing firms in Dar es salaam, Tanzania.Design/Methodology- Employing a case study research design, the study utilized a mixed-methods approach, integrating qualitative and quantitative methodologies. A total sample of 155 respondents was selected using simple random sampling for questionnaires, while 13 participants were purposively selected for in-depth interviews. Data collection involved structured questionnaires and interviews, analyzed using descriptive and inferential statistics with SPSS to ensure robust findings. Findings- The findings revealed a positive and significant influence of circular packaging on manufacturing firm performance. Adopting innovative packaging materials and clear disposal instructions can enhance competitive advantage, increase profit margins, and attract environmentally-conscious consumers, leading to higher market share and revenue. Practical Implications- The study highlights the importance of environmental sustainability practices for manufacturing firms in Tanzania. By adopting sustainable approaches, businesses can contribute to a healthier environment, reduce their carbon footprint, and promote responsible consumption. This can have positive implications for both the local community and the global ecosystem. The study recommends that firms invest in circular economic practices, such as innovative packaging and recycling. Policymakers are urged to provide incentives, such as tax relief and subsidies, to support green technologies. Collaboration between public and private sectors to fund research and development is also emphasized. Additionally, consumer advocacy for sustainable products and practices is critical to driving change